APPI/SPREAD Collective Action for Nutrition Social Audit Programme Odisha, India: Final evaluation report - Gordon, Jessica; Tranchant, Jean-Pierre; Casu, Laura; Mitchell, Becky; Nisbett, Nicholas (Institute of Development Studies, 2019)
This report summarises the background, design and methods, and key findings from an independent evaluation of the Collective Action for Nutrition (CAN) Social Audit programme designed and implemented by the Odisha-based non-governmental organisation (NGO) Society for Promoting Education and Rural Development (SPREAD) and supported by Azim Premji Philanthropic Initiatives (APPI). The evaluation was led by the Institute of Development Studies (IDS), UK in partnership with Development Corner Consulting (DCOR), India. Findings are intended to provide evidence on the effectiveness of the social audit model and feed into future plans for replication and scale-up.